2022
DOI: 10.1038/s12276-022-00729-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic escape of mitochondrial DNA triggers cGAS-STING-NLRP3 axis-dependent nucleus pulposus cell pyroptosis

Abstract: Low back pain (LBP) is a major musculoskeletal disorder and the socioeconomic problem with a high prevalence that mainly involves intervertebral disc (IVD) degeneration, characterized by progressive nucleus pulposus (NP) cell death and the development of an inflammatory microenvironment in NP tissue. Excessively accumulated cytosolic DNA acts as a damage-associated molecular pattern (DAMP) that is monitored by the cGAS-STING axis to trigger the immune response in many degenerative diseases. NLRP3 inflammasome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
98
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(101 citation statements)
references
References 62 publications
2
98
1
Order By: Relevance
“…The mechanism of IDD caused by pyroptosis is definite [ 41 ]; therefore, this study found that inflammatory factors IL1A, IL1B, NOD2, GBP1, IL6, AK1, EEF2K, and PYCARD were significantly altered in IVD after the intervention. Subsequently, WGCNA analysis was performed to identify the modules associated with cell scorching, and ultimately 11 candidate genes were retrieved from the intersection, namely, SMIM1, FBLN2, ZFP2, B4GALT5, HCRT, SLC6A17, MUSK, SLC26A8, CRHR2, SEZ6L2, and KCNJ15.…”
Section: Discussionmentioning
confidence: 87%
“…The mechanism of IDD caused by pyroptosis is definite [ 41 ]; therefore, this study found that inflammatory factors IL1A, IL1B, NOD2, GBP1, IL6, AK1, EEF2K, and PYCARD were significantly altered in IVD after the intervention. Subsequently, WGCNA analysis was performed to identify the modules associated with cell scorching, and ultimately 11 candidate genes were retrieved from the intersection, namely, SMIM1, FBLN2, ZFP2, B4GALT5, HCRT, SLC6A17, MUSK, SLC26A8, CRHR2, SEZ6L2, and KCNJ15.…”
Section: Discussionmentioning
confidence: 87%
“…This DNA-sensing pathway promotes SASP and mediates type-I interferon inflammatory responses to foreign viral and bacterial DNA as well as self-DNA ( 22 ). Cursory studies of NP cells and in vivo injury models have implicated the cGAS-STING pathway as an active inducer of senescence in the disc; however, this pathway in the disc is yet to be explored independent of chemical or mechanical insult ( 27 , 28 , 53 55 ). In this study, we clearly show STING is not a critical mediator of senescence onset and consequent degeneration in the disc.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a rat model of vertebral inflammation-induced intervertebral disc degeneration, where lipopolysaccharide (LPS) was introduced into vertebral defects, showed a degenerative phenotype marked by cartilaginous endplate defects, immune cell infiltration, and higher levels of cGAS, STING, TBK1, and IRF3 ( 27 ). Likewise, an acute injury model of disc herniation was used by Zhang et al to show that inhibition of STING results in the partial rescue of a degenerative phenotype by modulating NLRP3 signaling ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated cGAS-STING activation in a LPS vertebral injury-induced disc degeneration model; however, this activation was only achieved with the inflammatory stimulus of LPS and by breaching the integrity of the EP, enabling immune cell infiltration into the disc compartment (27). Similarly, a recent study showed the degenerative effects of needle puncture injury to rat discs were reduced when STING activation was attenuated by limiting mitochondrial DNA release from damaged mitochondria resulting from calcium overload (28). It is likely, however, that in the context of this acute herniation injury, infiltrating scavenging immune cells such as neutrophils and macrophages were the primary effectors of the cGAS-STING response and responsible for promoting inflammation; a similar immune response has been documented in the Tg197 mouse model, which overexpresses hTNF and is predisposed to spontaneous disc herniations (61).…”
Section: Discussionmentioning
confidence: 99%
“…This DNAsensing pathway promotes SASP and mediates type-I interferon inflammatory responses to foreign viral and bacterial DNA as well as self-DNA (22). Cursory studies of NP cells and in vivo injury models have implicated the cGAS-STING pathway as an active inducer of senescence in the disc; however, this pathway in the disc is yet to be explored independent of chemical or mechanical insult (27,28,(53)(54)(55). In this study, we clearly show STING is not a critical mediator of senescence onset and consequent degeneration in the disc.…”
Section: Discussionmentioning
confidence: 99%